1992
DOI: 10.1128/aac.36.11.2432
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and metabolism of racemic 2',3'-dideoxy-5-fluoro-3'-thiacytidine in rhesus monkeys

Abstract: 2',3'-Dideoxy-5-fluoro-3'-thiacytidine (FTC) is a nucleoside analog that selectively inhibits human immunodeficiency and hepatitis B viruses in vitro. In this study, the preclinical pharmacokinetics of racemic FTC in rhesus monkeys following intravenous and oral administration were characterized. The terminal half-life of FTC was independent of the route of administration and averaged 1.34 ± 0.18 h (mean ± standard deviation). Total clearance of FTC was moderate to high, averaging 1.49 ± 0.24 liters/h/kg. Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…To investigate the role of plasma virus and monocyte activation/ infection in CNS neuronal injury, we treated 2 SIV-infected, CD8 lymphocyte-depleted animals with CART beginning 28 days after infection, once we had confirmed by MRS significant decreases in NAA/Cr. CART consisted of treatment with PMPA and RCV (75,76). PMPA is a nucleotide analog that does not penetrate the CNS, and RCV is a nucleoside analog of a class that has low-to-nondetectable CNS penetration (40,(77)(78)(79).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the role of plasma virus and monocyte activation/ infection in CNS neuronal injury, we treated 2 SIV-infected, CD8 lymphocyte-depleted animals with CART beginning 28 days after infection, once we had confirmed by MRS significant decreases in NAA/Cr. CART consisted of treatment with PMPA and RCV (75,76). PMPA is a nucleotide analog that does not penetrate the CNS, and RCV is a nucleoside analog of a class that has low-to-nondetectable CNS penetration (40,(77)(78)(79).…”
Section: Methodsmentioning
confidence: 99%
“…Animals received daily injections of PMPA (30 mg/ kg) and RCV (10 mg/kg) s.c. Plasma and CSF specimens taken before and after initiation of CART were stored at -80°C, and RCV metabolites were analyzed by HPLC, as previously described (76).…”
Section: Methodsmentioning
confidence: 99%
“…The other two animals (98P009 and 97P021) were not given any drugs and served as no-therapy controls. PMPA is a nucleotide RT inhibitor that does not cross the brain-blood barrier (1,18), and FTC is a nucleoside RT inhibitor that crosses the blood-brain barrier (46).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, studies have shown that they select for different mutations on the HIV-1 reverse transcriptase gene in vitro, M184V for the (Ϫ) enantiomer and T215Y for the (ϩ) enantiomer (9,10). In addition these same studies showed that time to emergence of resistant virus in peripheral blood mononuclear cell culture was prolonged with RCV (14 weeks) compared to either lamivudine (3TC) (9 weeks) or (Ϫ)-FTC (9 weeks) (7,8; R. F. Schinazi, personal communication). This could be advantageous for a therapeutic regimen if the emergence of resistance mutations in patients were also delayed.…”
mentioning
confidence: 99%
“…A major advantage of using RCV would be that the virus would be challenged with two different compounds, which should increase the difficulty of developing resistance to both enantiomers (10). Both enantiomers are well absorbed orally and have demonstrated low toxicity in preclinical safety studies (1,2,3,4,8).…”
mentioning
confidence: 99%